An analysis of the contribution of donor aid to rural development in Zimbabwe : the case of Zhombe East 2013-2017. - Mujuru, Prayer K (Midlands State University, 2020)
The research aimed at analyzing the contribution of donor aid to rural development in Zimbabwe, taking Zhombe East as the case study from 2013-2017. This study was undertaken so as to have an evaluation on the work being done by donor organizations that are in Zhombe East on the rural community. Most of the development socially and economically in the area has much to do with donor organizations like Plan International however, there has been debate that these organizations have a hidden agenda. The researcher used the institutionalism and realism theories, this was employed in the bid to have an enhanced perceptive on the correlation between donor aid and rural development. Together qualitative and quantitative research methods were used in order to get the desired data for accurate conclusions. The study concludes that donor aid essentially contribute to rural development given the projects and programs that are being implemented in Zhombe East that are developing the rural community. In the area of Zhombe East there has been improvement in the education, employment Health, availability of nutritional food, school dropouts and awareness campaigns against early child marriages through the help of donor organizations. The researcher calls for the improvement of policies by the government that encourages more donor agencies to operate in Zimbabwe and for the government to work closely with donor organizations so as to come up with desired results. The study also recommends that donor organizations should engage more donor countries and institutions to get funding to enable them to carry out projects and programs that benefit more people in rural communities.